Prevalence and molecular characterisation of Acanthocephala in pinnipedia of the North and Baltic Seas. Issue 1 (April 2018) - Waindok, Patrick; Lehnert, Kristina; Siebert, Ursula; Pawliczka, Iwona; Strube, Christina
Abstract: Harbour seals ( Phoca vitulina ) and grey seals ( Halichoerus grypus ) are final hosts of acanthocephalans in the German North and Baltic Seas. Parasitic infections in seals can cause pathological changes, which may result in deteriorated health of the host. Common gastrointestinal parasites of harbour and grey seals are acanthocephalans and a number of 275 of 2460 (11.2%) investigated seals from 1996 to 2013 were infected with Corynosoma spp. (Acanthocephala, Polymorphidae). The prevalence showed a wave-like pattern: it increased from 1.2% and 0.4% in 1996 and 1997, respectively, to 23.9% during the second phocine distemper epizootic in 2002 and decreased to 6.2% in 2004. In 2005, prevalence peaked again with 25.0% followed by a decrease to 9.3% in 2009 and an increase to 38.5% in 2012. Statistical analysis revealed that harbour seals originating from the North Sea showed a higher prevalence than grey seals, whereas no significant difference between grey and harbour seals from the Baltic Sea was observed. Furthermore, juvenile pinnipedia from the North Sea were significantly less infected with Corynosoma spp. than seals older than seven month. Molecular species identification as well as phylogenetic relationship analysis among the detected Corynosoma species were achieved by sequencing and comparisons of the ribosomal ITS1-5.8S-ITS2-complex and cytochrome-c-oxidase I gene. Molecular analysis resulted in a newly arranged distribution of Acanthocephala in the North Sea as in contrast to previous studies, C. strumosum could not be confirmed as predominant species. Instead, C. magdaleni and a C. magdaleni isolate (isolate Pv1NS) with an atypical number of longitudinal rows of hooks at the proboscis were detected. Furthermore, morphological and molecular analyses indicate the possible finding of a cryptic species (Candidatus Corynosoma nortmeri sp. nov.). Graphical abstract: Image 1 Highlights: The prevalence of acanthocephalans in pinnipedia fluctuated between 1996 and 2013. Molecular analysis reveals new distribution of Acanthocephala in the North Sea. Proposed new species named Corynosoma nortmeri sp. nov. Use of molecular markers is crucial for a reliable species discrimination.